2020
DOI: 10.1002/ctm2.90
|View full text |Cite
|
Sign up to set email alerts
|

A new and rapid approach for detecting COVID‐19 based on S1 protein fragments

Abstract: The pandemic of novel coronavirus disease 2019 (COVID‐19) seriously threatened the public health all over the world. A colloidal gold immunochromatography assay for IgM/IgG antibodies against the receptor‐binding domain of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) S1 protein was established to assess its rapid diagnostic value. We first designed and manufactured all contents of the test cassette of SARS‐CoV‐2 rapid test kit: the colloidal gold‐labeled mouse‐antihuman lgM/lgG antibody, the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 17 publications
2
16
0
Order By: Relevance
“…The study was conducted to provide information on performance characteristics of commercially available serological assays. Thus, it contributes to previously described assessments [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ] and provides an additional piece of the puzzle in terms of interpreting the results of serological approaches for the retrospective diagnosis of infections with SARS-CoV-2.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…The study was conducted to provide information on performance characteristics of commercially available serological assays. Thus, it contributes to previously described assessments [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ] and provides an additional piece of the puzzle in terms of interpreting the results of serological approaches for the retrospective diagnosis of infections with SARS-CoV-2.…”
Section: Discussionsupporting
confidence: 52%
“…To close this diagnostic gap, there was an early focus on the implementation of antibody-based surveillance. By doing so, a more realistic view on the real dimensions of the spread of SARS-CoV-2 in the population was aspired to and numerous benchtop-based and point-of-care-testing (POCT)-based serological assays were introduced [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. However, the limitations of this strategy rapidly emerged as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(iv) It can accurately distinguish COVID-19 from other respiratory viral infections, such as influenza, and gives results quickly. Several LFIA methods for COVID-19 diagnosis based on anti-SARS-CoV-2 IgM/IgG combined test have been reported [ [15] , [16] , [17] ]. However, these other methods were based on colorimetric analysis, which results in low sensitivity and poor quantitative ability.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have confirmed that the global pandemic has caused a wide range of psychosocial problems( Brooks et al, 2020 ; Galea et al, 2020 ; Kisely et al, 2020 ; Naqos and Khouchani, 2020 ). As for people infected by SARS-CoV-2, who have attracted the most concern, great attention must be paid to their psychological problems, regardless of asymptomatic patients, patients with mild symptoms, or clinically cured patients( Bo et al, 2020 ; Mazza et al, 2020 ; Wu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%